Project based peer interaction to improve creativity and collaborative attitude of student: a mini review - I Setyowidodo; D Yulianto; Y S Pramesti (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2021)
Learning is currently more developed as an integrative science subject not as a discipline education, but as an applicative oriented education, the development of thinking skills, curiosity, the development of caring and responsible attitudes towards the social and natural environment. The current national character development policy is not in line with 2013 curriculum expectations, because it has not been able to shape Indonesian people who are more creative and of character. This study aims to implement Project Based Peer Interaction learning in an effort to improve students creativity and collaborative attitudes towards learning. The learning methods implemented in this learning are expected to have an impact on increasing students^ creativity and collaborative attitudes. Project Based Peer Interaction is a learning method focused on developing high-level thinking skills in project-oriented situations to solve shared problems and integrate new knowledge. The essence of this learning is the presentation of project based problems that are done together in a group to get the results of learning in an atmosphere of peer interaction